PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN MEMBELI TIKET PADA AGEN JASA MASKAPAI PENERBANGAN PT. GARUDA AIRLINES DI KOTA PALU - Puspitasari, Henny (Fakultas Ekonomi Universitas Tadulako, 2016)
This study aims to examine the simultaneous and partial influence of tangibles (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) on customer satisfaction (Y) in Garuda Airlines agent in Palu City. The type of research is descriptive-causal. Sampling technique is purposive sampling method. The results show that the dimensions of service quality consisting of physical evidence, empathy, reliability, responsiveness, and assurance simultaneously have a significant influence on customer satisfaction of buying tickets at Garuda Airline service agents. Partially, all the dimension of service quality have significant influence on the customer satisfaction of buying tickets at The Garuda airline service agent in Palu City.